Long‐Lived Liquid Marbles for Green Applications. (23rd June 2021) - Saczek, Joshua; Yao, Xiaoxue; Zivkovic, Vladimir; Mamlouk, Mohamed; Wang, Dan; Pramana, Stevin S.; Wang, Steven
Abstract: Liquid marbles allow for quantities of various liquids to be encapsulated by hydrophobic particles, thus ensuring isolation from the external environment. The unique properties provided by this soft solid has allowed for use in a wide array of different applications. Liquid marbles do however have certain drawbacks, with lifetime and robustness often being limited. Within this review, particle characteristics that impact liquid marble stability are critically discussed, in addition to other factors, such as internal and external environments, that can be engineered to achieve a robust long‐lived liquid marble. New emerging applications, which will benefit from this improvement, are explored such as unconventional computing, cell mimicry, and soft lithography. Incorporation of liquid marbles and liquid crystal technologies shows promise in utilizing structural color for optical display applications, and within green and environmental applications, liquid marble technology is increasingly adapted for use in energy conversion, heavy metal recovery, CO2 capture, and oil removal. Abstract : Liquid marbles offer unique and desirable properties for numerous applications. This review focuses on their more recent incorporation within green applications, such as carbon dioxide and oil capture. It considers how their lifetime and robustness can be improved to be better suited to real life functions, to ensure a more long‐lived and useful device.